The Role of Work Discipline in Mediating the Relationship Between Work Loyalty and Organizational Commitment to Employee Performance at PDAM Tirtasari Binjai - Mayna Antika Sari, Dian; Farida Ferine, Kiki (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2025)
This study aims to analyze the direct and indirect effects of work loyalty and organizational commitment on employee performance through work discipline as an intervening variable at PDAM Tirtasari Binjai in 2025. The research sample of 59 people from a total of 258 employees was determined using the Slovin formula and purposive sampling technique. Primary data were collected through questionnaires and analyzed using an associative quantitative approach with the SEM-PLS method through the SmartPLS 3 application. The results showed that work loyalty and organizational commitment had a positive and significant effect on work discipline but did not have a significant direct effect on performance. Work discipline was proven to have a positive and significant effect on performance and was the most dominant variable. Indirectly, loyalty and organizational commitment through work discipline had a significant effect on performance. Work loyalty and organizational commitment contributed 82.3% to work discipline, while the three together contributed 72.3% to employee performance.